Meta Analisis: Problem Based Learning (PBL) Terhadap Kemampuan Pemahaman Konsep Peserta Didik - Muh. Fairus Ismail; Yuliany, Nur; Savitri, Dewi (Alauddin Journal of Mathematics Education, 2022)
The purpose of this study is to determine: 1) the influence of Problem Based Learning on the understanding of students’ concepts as a whole; 2) the influence of Problem Based Learning on the understanding of student concepts in terms of education level; 3) the influence of Problem Based Learning on students’ understanding of concepts reviewed from the year of publication. The method used in this study is a quantitative method with a meta-analysis research design and the type of research used is the Type of Group Contrasts. Data collection is carried out by researchers by looking for publication articles that are relevant or related to the topic to be studied on internet network sites in the form of Google Scholar, Repositories, and Open Knowledge Maps. The sampling technique uses purposive sampling technique. The instrument used is a data code sheet that summarizes data and data information. The data were analyzed by calculating the value of the effect size using the standardized means difference formula. Based on the analysis carried out obtained: 1) The Problem Based Learning method as a whole is effective (significant) in improving students’ concept understanding ability, 15 published articles with a mean effect size of 0.773, and are classified as large categories; 2) The Problem Based Learning method based on the level of education is effective (significant) in improving students’ concept understanding ability. At the junior high school level, 9 publication articles were found with an average effect of 0.785 and were classified as large categories, while at the high school level, 6 publication articles were found with an average effect of 0.754 and classified into large categories; 3) The Problem Based Learning method based on the year of publication is effective (significant) in improving students’ concept understanding ability.